Uranium from seawater – Infinite resource or improbable aspiration?. (August 2017) - Dungan, K.; Butler, G.; Livens, F.R.; Warren, L.M.
Abstract: The availability of uranium drives the future of the nuclear energy industry; an upper limit on uranium prices will determine whether it is economically viable to continue utilising the present generation of light water reactors (LWRs). The alternative is a move towards fast reactors, which use less uranium than LWRs, however require substantial investment and development, and might never become economically viable unless uranium prices rise considerably. While terrestrial uranium resources are seen to be limited, there are approximately 4 billion tonnes of uranium in seawater and although uranium only exists at concentrations of around 3.3 ppb, selective extraction has been achieved. Even though several thorough cost estimates of the extraction process have been undertaken, the practicality of the process and the scale on which it would need to be deployed to sustain the nuclear industry is still questionable. This review aims to examine some of the limitations of the current favourite amidoxime braid system, as well as examining possible interactions with existing legal frameworks which have been put in place; in particular those protecting the marine environment. The potential for uranium extraction from seawater is clearly vast, together with the consequences for nuclear technology choices - but the implications of deploying the technology on such a large scale must be considered. Graphical abstract: Highlights: A discussion of the effects of uranium from seawater on nuclear systems choices. The requirements necessary to supply the global nuclear energy sector are studied. Potential flaws have been examined, including legal frameworks within maritime law. Considerations include feasibility and the environmental implications of deployment.